2002
DOI: 10.1006/jmsc.2001.1300
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependent otolith growth of larval and early juvenile Atlantic cod (Gadus morhua)

Abstract: The otolith (lapillus) size-fish size relationship was examined for offspring of two Atlantic cod stocks, reared at different temperatures. Larvae and early juveniles reared at high temperatures (fast growing), had larger otoliths at a given length than fish reared at low temperatures (slow growing). Within a given temperature group, however, faster growing cod tended to have proportionally smaller otoliths, although the difference was not always significant. Moreover, the otolith radius of Norwegian coastal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
38
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 11 publications
6
38
2
Order By: Relevance
“…A peak in the otolith growth rate, observed at around 53 mm in SL, differs from the length when the somatic growth is at a maximum, at around 82 mm in SL. A similar lag has been observed for other fish species (Secor and Dean, 1989;Folkvord et al, 1997;Otterlei et al, 2002), which indicates that there is not a simple proportional relationship between otolith growth and somatic growth. In terms of the function of the otolith, it may be important for young individuals to attain otoliths of a certain size quickly, while somatic growth may increase or decrease more variably under different conditions (Popper and Coombs, 1980;Neuman et al, 2001).…”
Section: Discussionsupporting
confidence: 75%
“…A peak in the otolith growth rate, observed at around 53 mm in SL, differs from the length when the somatic growth is at a maximum, at around 82 mm in SL. A similar lag has been observed for other fish species (Secor and Dean, 1989;Folkvord et al, 1997;Otterlei et al, 2002), which indicates that there is not a simple proportional relationship between otolith growth and somatic growth. In terms of the function of the otolith, it may be important for young individuals to attain otoliths of a certain size quickly, while somatic growth may increase or decrease more variably under different conditions (Popper and Coombs, 1980;Neuman et al, 2001).…”
Section: Discussionsupporting
confidence: 75%
“…This is an interesting finding because daily growth increments are known to be deposited in concentric rings on the fish otoliths (Tanaka et al 1981;Neilson and Geen 1982), thus we expected that the coefficients of determination for OL and OW would have been equivalent within each season. Coefficients of determination between otolith growth and somatic growth much greater than observed here have been reported for juveniles of other fish (Waessle et al 2003), even over a range of environmental conditions (Otterlei et al 2002). We showed that the modest relationships between the otolith metrics and somatic size in the present study were due to the extreme treatment combination of the hot water temperature and low food ration during summer and complete food deprivation during winter.…”
Section: Discussioncontrasting
confidence: 55%
“…Such deviations from direct proportionality in the otolith-to-somatic size relationship can be driven by variation in growth rate, leading to similar-sized fish with different-sized otoliths (growth effect; Reznick et al 1989). For example, the cessation of somatic growth could occur during periods of food deprivation (Wright et al 1990) or at extreme water temperatures (Otterlei et al 2002), but the accretion of CaCO 3 continues, causing an increase in the size of the otolith without a corresponding increase in fish size. Alternatively, faster-growing fish that have smaller otoliths may be younger (age effect) than similar-sized slower-growing fish with larger otoliths (Secor and Dean 1992).…”
Section: Discussionmentioning
confidence: 99%
“…However, a number of investigations indicate that under natural conditions it is difficult to distinguish changes in otolith width related to feeding conditions from changes caused by temperature fluctuations (e.g. Otterlei et al 2002, Fey 2005.…”
Section: Discussionmentioning
confidence: 99%
“…Much focus has been directed to the influence of environmental variability, of which temperature and prey availability are believed to have the greatest influence. Studies suggest that surviving larvae grow close to their size-and temperature-dependent capacity (Otterlei et al 2002, Folkvord 2005; however, the influence of temperature and prey availability are interlinked, and specific temperature optima for growth occur under food limited conditions (Buckley et al 2004).…”
Section: Introductionmentioning
confidence: 99%